To solve the equation \( x^2 - 36 = 0 \) by factoring using the difference of squares pattern, we can recognize that \( x^2 - 36 \) can be written as:
\[ x^2 - 6^2 = 0 \]
This can be factored using the difference of squares formula, which states that \( a^2 - b^2 = (a - b)(a + b) \). Applying this to our equation:
\[ (x - 6)(x + 6) = 0 \]
Now, we set each factor equal to zero:
- \( x - 6 = 0 \) → \( x = 6 \)
- \( x + 6 = 0 \) → \( x = -6 \)
Therefore, the solutions are:
\[ x = 6 \quad \text{and} \quad x = -6 \]
The correct answers from your responses are:
x=6, x=−6 and x equals 6 , x equals negative 6.